THE MODEL OF RELATIONS BETWEEN THE STATE AND RELIGIOUS ORGANIZATIONS AND ITS IMPLEMENTATION IN THE REPUBLIC OF LATVIA - Macuka, Jekaterina (Via Latgalica, 2009)
Models of relations between the state and religious organizations and the basic principles of their implementation are analyzed with the aim to determine which model of relations is being realized in the Republic of Latvia as well as to establish whether a model of relations, secured by a normative act, corresponds to the one implemented in practice. Within this work, the method of analysis has been used when considering the models of relations between the state and religious organizations, as well as the comparative method in the comparison of application of the basic principles of these models in the Republic of Latvia. The relations between the State and religious organizations are examined from the administratively legal and constitutionally legal aspect. The normative acts of the Republic of Latvia are discussed, as well as their mutual interaction and the collisions having sprung up between them. Laws and regulations of the Republic of Latvia are evaluated in connection with the norms of other European Union Member States, which regulate the relations between the state and religious organizations, and their experience. Evaluating the practice of other countries and the implemented models of relations between the state and religious organizations monographs and scientific papers by the scientists of the respective countries have been used. The content of international legal norms regulating freedom of religion have been analyzed as well as the requirements of the normative acts of the Republic of Latvia and their interaction. As grounds for conclusions, rulings by the court are chosen in cases where the application of legal norms is adjudicated concerning the realization of the right to the freedom of religion. Three fundamental principles are pointed out in the research basing on which the relations between the state and religious organizations are formed: association between the state and religious organizations, cooperation between the state and religious organizations and segregation between the state and religious organizations. Basing on the abovementioned principles, all models of relations between the state and religious organizations are formed. The model being implemented in a state can be determined by the regulation of the activity of religious organizations ensured with normative acts, by the range of rights of religious organizations, by peculiar features of preconditions, by the range of privileges, and by the burden of responsibilities imposed on religious organizations. To a large extent, the model of relations between the state and religious organizations depends on state traditions, historical development, distribution and impact of the definite religion within the state territory. The principle of unity between the state and religious organizations indicate the unity between them, institutions of religious organizations are identified as state institutions. Implementation of the abovementioned principle can manifest as an absolute unity between the state and church when state laws are based on definite religious norms and, in case of collisions, the principles of religious doctrine are applied. Or, within the abovementioned principle, two models of relations can be distinguished: a model of religious state and a model of state religion (church). The principle of cooperation between the state and religious organizations provides for separation of the state and religious organizations, they are functioning as autonomous subjects, religious organizations form their own structure and define their inner administration, the state on its part does not interfere in the inner affairs of religious organizations. Nevertheless, the state and religious organizations cooperate in order to achieve definite aims. Such a model of cooperation can be called the model of cooperation. In countries where the principle of separation of the state and religious organizations is in force and the model of segregation is functioning, the autonomy of religious organizations and the state are strictly separated. Each of these subjects is functioning in its own sphere, in parallel to one another. Religious organizations are not vested the rights to perform the functions of the state, and they do not receive financial support. Registration of a religious organization is the starting point where the activities of the state and of religious organizations come into contact. Registration of a religious organization is a basis for the model of relations between the state and religious organizations to be implemented in the given country. In the Republic of Latvia, the process of registration of religious organizations is regulated by the Law on Religious Organizations which provides for the order of registration of religious organizations as well as the legal status of the religious organizations to be registered; registration has a multi-stage structure. Initially, a congregation is registered as reregistrable, but later it acquires a regular status and after uniting the congregations can form a religious union (church). Religious unions (churches) have the right to establish dioceses and institutions. The next step in the mentioned chain includes religious organizations whose relations with the Republic of Latvia can be regulated by special laws. The State has established special relations with Evangelical Lutheran, Roman Catholic, Orthodox, Old Believer, Methodist, Baptist, Seventh-day Adventist and Moses faith (Judaist) denominations. These denominations have a peculiar status in the Republic of Latvia, the range of their rights differs from the rights of other congregations. Relations between the religious unions (churches) of these denominations and the State are regulated by special laws that define their rights and status. The Latvian Constitution (Satversme) contains a reference to the model of relations between the Republic of Latvia and religious organizations providing that the State is separated from the church. Evaluation of the features of a model of separation and its application to the relations between the Republic of Latvia and religious organizations allows to determine whether the implemented model is a model of separation or whether the relations between the State and religious organizations realized in practice belong to quite another model. The requirement for autonomy of religious organizations and the State can be regarded as satisfied, since the demand for non-interference by the State in the inner activities of religious organizations (except for the cases of violating laws) is included in the Law on Religious Organizations. Separation of religious organizations from the public rights sector presently is not being implemented. In state schools there are religious instruction lessons, religious organizations carry out religious activity in medical institutions and prisons, a service of chaplains has been established whose activity is funded from the state budget. Equality of the forms of activity of religious organizations is not guaranteed, since there exists a multi-stage registration system. A state function of performing marriage ceremonies is delegated to religious organizations. Thus, state functions are delegated to religious organizations. Besides the religious organizations are offered direct and indirect financial support which manifests in allotting tax relief as well as allocating direct grants from the state budget. The model having been established in the Republic of Latvia is a model of cooperation between the State and religious organizations. In the Constitution no state religion is provided but also no segregation of the State and religious organizations is realized. The State acknowledges the autonomy of religious organizations, however, the religious organizations receive financial support, definite functions are delegated to them, and religious organizations are operating in the public sector. Satversme lacks provisions that would truly provide that no state church exists in Latvia, but at the same time definite procedures and operations are being delegated to the church as stated by the law. The idea of amending the Satversme of the Republic of Latvia ought to be considered that would contain the provision about the model of cooperation between the State and religious organizations being realized in practice.